Effect of fertigation strategies on growth and production of soilless cucumber (Cucumis sativus) - RANDHE, RAVINDRA D; HASAN, MURTAZA; SINGH, D K; KUMAR, S NARESH; KUMAR, PRAMOD; ALAM, WASI; PANDEY, RAKESH (The Indian Journal of Agricultural Sciences, 2022)
Weight-based fertigation scheduling strategies optimized for cucumber production in coco-peat grow bag under greenhouse conditions. The experiment was conducted using treatments comprised of four different levels of nutrient solution replenishment based on weight loss of growing bags along with plants, viz. full replenishment, 10% and 20% less replenishment and 20% more replenishment. Significantly, maximum cucumber yield (96.88–104.89 t/ha), number of fruits per plant (25–25.33) and yield per plant (2.42–2.62 kg/plant) were observed under full replenishment of nutrient solution against weight loss. It was also at par with treatment, which received 20% more nutrient solution as compared to full replenishment. The physiological attributes, viz. plant height (184 cm), number of nodes per plant (29.33), dry biomass and root parameters were observed higher in the full replenishment strategy which received 100% fertigation against the weight loss. Water use efficiency was found higher in the full replenishment followed by 20% less replenishment and lowest (811.38 kg/ha-mm) in 20% more replenishment of nutrient solution. Fertigation strategy which received the 100% nutrient solution against the weight loss, allowed the plant to grow fully with maximum yield and water use efficiency (WUE). Hence, 100% and more replenishment of nutrient solution against weight loss were found to be highly suitable strategies for controlling the fertigation scheduling through the weightbased sensing system.